Pengaruh Penambahan EM4 Pada Pembuatan Biogas dengan Bahan Baku Kotoran Sapi Menggunakan Digester Fix Dome Sistem Batch - Wicaksono, Aria; Amalia, Rif?ah; Gayuh Prasetya, Hendrik Elvian (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2019)
Biogas is a gas produced from the fermentation process of organic materials bymicroorganisms in closed conditions (anaerobic). Biogas consists of ± 60% CH4 (methane), ±38% CO2 (carbon dioxide), ± 2% N2 (nitrogen), O2 (Oxygen), H2 (hydrogen), and H2S(hydrogen sulfide). In this research, the making of biogas uses raw materials from cow dung.Cow dung is the right raw material because it contains methane-producing bacteria. Thisresearch aims to determine the influence of the EM4 addition of biogas quality produced. Thisresearch was conducted in the Basic laboratory system of energy generation of the SurabayaState Polytechnic electronics. The method of the research is to use a comparison of cow andwater in raw materials, with a ratio of 1:1 with the addition of EM4 (Effective microorganism)as much as 3 liters on variations of 1 and 1.5 liters on variation 2. Biogas making is carried outon the digester with a volume of 200 liters with a batch system with stirring 3 times a day withfermentation for 25 days. The result of this research is with the addition of EM4 as much as 3liters produce biogas with methane gas content with the amount of 53.6%. The resulting biogascombustion test has a yellowish blue flame, a long flame of 56 seconds. While the addition ofEM4 with a total of 1.5 liters produces biogas with methane gas content with the amount of46.8% yellow flame color with a long flame of fire for 34 seconds